2008
DOI: 10.1017/s0021932007002441
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors Associated With Alcohol Abuse in Moshi, Northern Tanzania

Abstract: Summary. This study aimed to assess the prevalence of and risk factors associated with alcohol abuse among women and men in Moshi in northern Tanzania. Alcohol abuse was measured by a CAGE score of 2-4, versus 0-1 for no alcohol abuse (Ewing, 1984). Crude and adjusted logistic regression models determined odds ratios (OR) and 95% confidence intervals (95% CI) of alcohol abuse by characteristics of, respectively, women with partners (n=1200), women without partners (n=614) and men (n=788) (women's partners). Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…While only 7% of women with partners and 9.3% of women without partners were classified as probable or definite problem drinkers in a population-based survey in Moshi [30], 37% of our study participants were classified as having probable or definite problem drinking on the same alcohol scale. This indicates that problem drinking is a major public health concern among women working in these settings and effective interventions are needed to address this issue.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…While only 7% of women with partners and 9.3% of women without partners were classified as probable or definite problem drinkers in a population-based survey in Moshi [30], 37% of our study participants were classified as having probable or definite problem drinking on the same alcohol scale. This indicates that problem drinking is a major public health concern among women working in these settings and effective interventions are needed to address this issue.…”
Section: Discussionmentioning
confidence: 54%
“…The population based study found Christian women were more likely to be problem drinkers in the same area [30]. These observations present an opportunity to engage religious leaders in future alcohol abuse prevention initiatives.…”
Section: Discussionmentioning
confidence: 78%
“…Two further studies among women, one by Sa and Larsen, (2008) on the same data set, and another by Zuma et al (2003) conducted in Carletonville, South Africa corroborated these findings. A later study among the aforementioned community in Moshi, Tanzania, found no significant relationship between HIV infection and alcohol abuse (CAGE score of 2 -4) by women or men (Mitsunaga & Larsen, 2008). …”
Section: Original Articlementioning
confidence: 89%
“…In another study using data from the same community-based survey, Mitsunaga and Larsen (2008) The association between self-reported alcohol use before sex, physical violence/sexual coercion in the past and HIV prevalence was examined in a sample of young women from a population-based cohort in Rakai, Uganda (Zablotska et al, 2009 …”
Section: Community/population-based Studiesmentioning
confidence: 99%
“…An additional eight nonoverlapping studies published prior to 2009 were identified from our previous narrative review (Allen et al, 1992;Bassett et al, 1996;Clift et al, 2003;Dunkle et al, 2004;Fisher, Cook, Sam, & Kapiga, 2008;Msuya et al, 2006;St. Lawrence et al, 2006;Zablotska et al, 2009) and three additional studies reported in Pithy and Parry (2009) (Mitsunaga & Larsen, 2008;Mmbaga et al, 2007;Seme, Mariam, & Worku, 2005). These additional three studies were likely not included in our review due to the use of different electronic databases (PsycINFO vs. PubMed).…”
Section: Methods Literature Reviewmentioning
confidence: 99%